Enhancement the productivity of drum solar still utilizing parabolic solar concentrator, phase change material and nanoparticles' coating. (1st November 2022) - Alqsair, Umar F.; Abdullah, A.S.; Omara, Z.M.
Abstract: This study aims to improve fresh water productivity from seawater or brackish water utilizing renewable energies by a solar desalination system, so an experimental study conducted to improve the performance of the drum solar still (DSS) utilizing transparent walls of SS, parabolic solar concentrator (PSC), phase change material (PCM), nanoparticles' coating (NC) and external condenser. PSC will be utilized to concentrate sun rays on the drum's back side, which raised the rate of evaporation, but the high temperature of the glass due to the presence of the PSC has a negative impact on the solar still's condensation rate. Two different methods used to solve the problem of high temperature of the glass to increase the productivity of the DSS, the first, using a fan to draw the generated vapor and condense it in an external condenser and the second is use of PCM-Ag mixture to absorb the excess energy in times of intense radiation and recover it after that at the time of low radiation. The results indicated that, the boiling point of saline water inside the DSS was reached using the new design of the DSS basin, which led to a significant increase in the amount of evaporation. Additionally, the maximum improves in DSS productivity when utilized NC, PSC and external condenser was achieved at 0.3 rpm, where the production enhancement was around 320 % with efficiency of 72 %. Highlights: Drum still performance with and without Ag-nanoparticles' coating was studied. Effect of utilizing parabolic solar concentrator, external condenser and PCM-Ag was investigated. The optimum speed of drum utilizing external condenser, PSC and PCM was 0.3 rpm. Productivity rise of DSS with PSC and PCM-Ag was 310 %%. The modified DSS is capable to mitigate 14.1 tons of CO2 per year.